Peran Guru Kristen Untuk Menanamkan Kedisiplinan Siswa Melalui Metode Pembiasaan dalam Pembelajaran Daring [The Role of Christian Teachers in Cultivating Discipline for Students Through the Method of Habituation During Online Learning] - Patrychia Talakua; Kurniawati Martha (Universitas Pelita Harapan, 2022)
The pandemic caused by Covid 19 has made changes in learning. Previously, students came to school to study in class and meet directly with the teachers. Now, learning has been done online, where students learn from home. During this online learning, there were several problems related to discipline which caused the learning atmosphere to be less conducive. Based on these problems, the aim of the research is the application of the habituation method by Christian teachers can help students familiarize themselves to Christian values in applying discipline during online learning. The research method is descriptive qualitative research method by taking data based on observations and teaching results during the implementation of the Field Experience Practicum and literature study. The research shows that the application of habituation methods can shape student discipline during online learning. Therefore, it is concluded that the habituation method can be applied and suggested to the teachers in helping students have noble character through habituation in applying student discipline during online learning.